Edukasi Dasar Investasi Bagi Pelajar Tingkat Sekolah Menengah Kejuruan (SMK) - Adelina Suryati; Renanda Renanda; Rani Sukma Ayu; Anggita Inah Safitri; Sarah Khairunnisa; Syafrizal Syafrizal; Suparjono Suparjono; Dimas Novianto; Bazatulo Laia (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The financial literacy level in Indonesia, particularly among vocational high school (SMK) students, remains low. Limited understanding of investments and the high risk of falling victim to fraudulent schemes are major concerns. This financial literacy seminar aimed to provide basic knowledge about investments, their types, steps to start investing, and characteristics of fraudulent investments. The seminar was conducted at an SMK in Bekasi using an interactive lecture method and was attended by 45 students. The seminar began with material presentation, followed by a Q&A session and an interactive quiz. The results showed that most participants understood the material and were able to distinguish between low-risk and high-risk investments. Approximately half of the participants actively engaged in discussions, indicating increased awareness of the importance of financial literacy. Participants responded positively to the seminar and expressed interest in similar programs with different themes in the future. In conclusion, this seminar effectively improved the financial literacy of SMK students and made a positive contribution to building a financially aware younger generation.